2019
DOI: 10.1111/vsu.13276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cross‐sectional geometrical properties and bone density of the proximal radius between Saint Bernard and other giant breed dogs

Abstract: Objective: To compare the geometrical properties and bone mineral density (BMD) of the proximal radius between Saint Bernard and other giant breed dogs. Study design: Observational, cross-sectional, descriptive study. Animals: Thirteen client-owned Saint Bernard dogs and 13 other client-owned giant breed dogs. Methods: Computed tomography (CT) studies of Saint Bernard and other giant breed dogs were reviewed. Multiplanar reconstruction of the CT images was used to determine cross-sectional variables at the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Additionally, OIASC and/or HA treated groups were found to possess a higher resistance to torsional force, based on the higher PMI values determined by μCT. PMI provides a rough estimate of torsional rigidity by determining the distribution of bone around the center of the specimen, it is inversely related to shear stress created in the bone (Schoenau et al, 2001; Bagi et al, 2006; Mejia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OIASC and/or HA treated groups were found to possess a higher resistance to torsional force, based on the higher PMI values determined by μCT. PMI provides a rough estimate of torsional rigidity by determining the distribution of bone around the center of the specimen, it is inversely related to shear stress created in the bone (Schoenau et al, 2001; Bagi et al, 2006; Mejia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these outcomes were likely the consequence of variations in the cortical region surrounding the bones. Prior analysis of cortical bone in the dog radius and ulna has been conducted by [ 6 , 7 , 29 ]. The investigations revealed a consistent pattern wherein smaller breeds exhibited thinner cortices and smaller cortical bone regions than larger breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The MOI is essential in determining how resistant a structure is to bending deformation. Higher MOI craniocaudal and mediolateral values indicate higher bone resistance to bending forces in the craniocaudal and mediolateral planes [ 29 ]. However, the cadaver test is prohibitively expensive due to the limited number of specimens that can be obtained, making it difficult to carry out many experiments considering different boundary conditions.…”
mentioning
confidence: 99%
“…One dog, a Saint Bernard, had a fracture of the proximal radius. A study has found that the proximal radius in the Saint Bernard possesses significant differences in structural properties, such as lower cortical thickness and moment of inertia as well as bone mineral density . These findings suggest that the Saint Bernard is at higher risk of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that the proximal radius in the Saint Bernard possesses significant differences in structural properties, such as lower cortical thickness and moment of inertia as well as bone mineral density. 44 These findings suggest that the Saint Bernard is at higher risk of fractures. Another risk factor for the fracture was having removed 63% of the radius.…”
Section: Complicationsmentioning
confidence: 93%